2009
DOI: 10.1007/s11033-009-9878-7
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of Otis tarda (Gruiformes: Otididae) and phylogeny of Gruiformes inferred from mitochondrial DNA sequences

Abstract: The complete nucleotide sequence of mitochondrial genome of the Great bustard (Otis tarda) was determined by using polymerase chain reaction (PCR) method. The genome is 16,849 bp in size, containing 13 protein-coding, 2 ribosomal and 22 transfer RNA genes. Sequences of the tRNA genes can be folded into canonical cloverleaf secondary structure except for tRNA-Cys and tRNA-Ser (AGY), which lose "DHU" arm. Sequence analysis showed that the O. tarda mitochondrial control region (mtCR) contained many elements in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 46 publications
4
28
0
Order By: Relevance
“…In our current study, the family Aramidae (e.g., A. guarauna) was embedded in the clade of traditional Gruidae with strong support in the NJ (Figure 3 Figure 6) trees (87% bootstrap values, 50% bootstrap values, 87% bootstrap values, and 0.51 posterior probability values, respectively). The same topology (with Aramidae as a close sister to Gruidae) has been reported in several studies (Fain et al, 2007;Livezey, 1989;Yang et al, 2010b). Livezey (1998) showed that the families Aramidae and Gruidae both belong to the superfamily Gruoidea, but the family Rallidae belongs to the order Ralliformes as opposed to the order Gruiformes.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…In our current study, the family Aramidae (e.g., A. guarauna) was embedded in the clade of traditional Gruidae with strong support in the NJ (Figure 3 Figure 6) trees (87% bootstrap values, 50% bootstrap values, 87% bootstrap values, and 0.51 posterior probability values, respectively). The same topology (with Aramidae as a close sister to Gruidae) has been reported in several studies (Fain et al, 2007;Livezey, 1989;Yang et al, 2010b). Livezey (1998) showed that the families Aramidae and Gruidae both belong to the superfamily Gruoidea, but the family Rallidae belongs to the order Ralliformes as opposed to the order Gruiformes.…”
Section: Discussionsupporting
confidence: 77%
“…Opinions on the systematic relationships of Gruiformes are as diverse as the families included within it. Despite ongoing debate over monophyly of the order and relationships among its various members, recent opinions have converged on the monophyly of a 'core' group of five families classified as the suborder Grues: the rails (Rallidae), the cranes (Gruidae), the limpkins (Aramidae), the trumpeters (Psophiidae), and the finfoots (Heliornithidae) (Hackett et al, 2008;Yang et al, 2010b). A consensus has begun to emerge that there is a monophyletic 'core' consisting of Gruidae, Aramidae, Psophiidae, Heliornithidae, and Rallidae (Fain et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations